Synthesis and Characterization of Cobalt Nanoparticles Using Hydrazine and Citric Acid - S. A. Salman; T. Usami; K. Kuroda; M. Okido (Journal of Nanotechnology)
Cobalt nanoparticles were produced by employing the liquid-phase reduction method and hydrazine. The effect of citric acid additives on the formation and growth mechanism of cobalt nanoparticles was investigated using polarization methods. The cobalt nanoparticles produced in 0.2 M cobalt sulfate and 5 M hydrazine at 298 K had a spherical shape with a diameter of 400 nm. The dendritic nanoparticles formed with the decreasing of hydrazine concentration at 298 K. On the other hand, dendritic large particles are confirmed at 353 K. It was confirmed that the reduction reaction progressed with the addition of citric acid, and a hexagonal close-packed (εCo) phase was formed.